2009
DOI: 10.1080/15622970701870933
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal remodelling after MDMA neurotoxicity: A single case study

Abstract: Acute ingestion of MDMA (ecstasy) causes a transient marked increase in serotonin and dopamine at central synapses. Recent studies demonstrated that MDMA induces damage of serotonergic nerve terminals and alters hippocampal processing. Pronounced cognitive deficits in MDMA users affect learning and memory abilities. This pattern of predominant and long-lasting memory dysfunction suggests that the functioning of the hippocampus might be affected by the neurotoxic effects of MDMA. We present the case of a 16-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Moreover, the same cohort of MDMA users, although not displaying overt behavioral abnormalities, reported subnormal mood and exhibited modest, non-significant, deficits in some tests of attention and memory, which might M a n u s c r i p t 19 potentially stem from the decrease in SERT binding sites . Although the occurrence of psychotic disorders in MDMA users has not been as thoroughly studied as METHassociated psychosis, alterations in hippocampal activity could potentially contribute to the documented ability of MDMA to induce psychotomimetic effects (Nifosi et al, 2009;Potash et al, 2009;Patel et al, 2011).…”
Section: Studies In Humansmentioning
confidence: 99%
“…Moreover, the same cohort of MDMA users, although not displaying overt behavioral abnormalities, reported subnormal mood and exhibited modest, non-significant, deficits in some tests of attention and memory, which might M a n u s c r i p t 19 potentially stem from the decrease in SERT binding sites . Although the occurrence of psychotic disorders in MDMA users has not been as thoroughly studied as METHassociated psychosis, alterations in hippocampal activity could potentially contribute to the documented ability of MDMA to induce psychotomimetic effects (Nifosi et al, 2009;Potash et al, 2009;Patel et al, 2011).…”
Section: Studies In Humansmentioning
confidence: 99%
“…Meth-induced decreases in sensorimotor gating have been attributed to alterations in both glutamate and downstream GABA neurotransmission in cortico-striatal-thalamic-cortical sensory filtering circuits (Arai et al, 2008, Mizoguchi et al, 2009). Prolonged psychosis has also been reported after MDMA use, and although this has not been studied as in-depth as Meth-associated psychosis, alterations in hippocampal activity could potentially contribute to the psychotomimetic effects of MDMA (Nifosi et al, 2009, Potash et al, 2009, Patel et al, 2011). …”
Section: Consequences Of Neurotoxicitymentioning
confidence: 99%
“…Our results are also consistent with the results of brain imaging studies showing ecstasy-related structural and functional alterations in the medial temporal regions that underline this cognitive function. It is of interest that neuroimaging studies in ecstasy users have found a reduced left hippocampal metabolism at resting state (Obrocki et al, 1999) and reduced left hippocampal activation during an episodic memory paradigm (Daumann et al, 2005), as well as a strong association between this pattern of predominant memory dysfunction and a reduced activation on hippocampal regions (Nifosi et al, 2008). This suggests that the functioning of the hippocampus might be affected by the neuromodulatory effects of ecstasy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, clustering/switching analyses could contribute to the understanding of the brain substrates of ecstasy-induced cognitive deficits, as different studies point to temporal versus frontal-striatal dysfunction in ecstasy users (Fox et al, 2002;Quednow et al, 2006). Structural brain imaging studies, for instance, suggest that MDMA polydrug users showed multiple regions of reduced brain grey matter concentration including left prefrontal cortex (Cowan et al, 2003) and also hippocampus bilaterally (Nifosi et al, 2008). Recent studies using functional magnetic resonance imaging (fMRI) suggest differences in the activation of the hippocampus between MDMA users and healthy controls during working memory tasks and so supported the view of a hippocampal dysfunction in MDMA users (Daumann et al, 2005;Jacobsen et al, 2004;Moeller et al, 2004).…”
mentioning
confidence: 99%